TWITTER AS A TECHNOLOGY FOR AUDIENCING AND FANDOM: The #Eurovision phenomenon - Highfield, Tim; Harrington, S.; Bruns, A. (2013)
Amongst the most prominent uses of Twitter is its role in the discussion of widely televised events: Twitter's own statistics for 2011, for example, list major entertainment spectacles (the MTV Music Awards and the BET Awards) and sports matches (the UEFA Champions League final and the FIFA Women's World Cup final) amongst the events generating the most tweets per second during the year. During such major media events, Twitter is used most predominantly as a technology of fandom: it serves as a backchannel to television and other streaming audiovisual media, enabling users offer their own running commentary on the universally shared media text of the event as it unfolds live. This article examines the use of Twitter as a technology for the expression of shared fandom in the context of a major, internationally televised annual media event: the Eurovision Song Contest. Our analysis draws on comprehensive data sets for the 'official' event hashtags, #eurovision, #esc, and #sbseurovision. Using innovative methods that combine qualitative and quantitative approaches to the analysis of Twitter data sets containing several hundreds of thousands, overall patterns of participation to discover how audiences express their fandom throughout the event are examined. Such analysis is able to provide a unique insight into the use of Twitter as a technology for fandom and for what in cultural studies research is called 'audiencing': the public performance of belonging to the distributed audience for a shared media event. The work points to Twitter as an important new medium facilitating the connection and communion of fans. © 2013 Copyright Taylor and Francis Group, LLC.